Relativisation in Maltese. (31st July 2015) - Camilleri, Maris; Sadler, Louisa
Abstract: We develop a detailed description of the differences and similarities between the syntax of restrictive and non‐restrictive relative clauses in Maltese. We show that Maltese makes use of both a complementiser strategy and a wh‐pronoun strategy in each type of relative clause. We discuss in some detail the ways in which the distribution of gaps and resumptive pronouns differs between these two strategies, being heavily constrained in the case of the wh‐pronoun strategy. The discussion highlights some differences between the standard and dialectal varieties of Maltese, especially in regard to wh‐relatives. Beyond these major strategies, we illustrate two further relative constructions, a highly constrained bare relativisation strategy for restrictive relativisation and a further wh‐pronoun strategy found only in non‐restrictives. While the main focus of this paper is a synchronic description of relativisation in Maltese, we draw a number of comparisons between Maltese and some Arabic dialects, in particular the Western dialects to which Maltese is closely related.